Navigation-Related Structural Change in the Hippocampi of Taxi Drivers - Maguire, Eleanor A.; Gadian, David G.; Johnsrude, Ingrid S.; Good, Catriona D.; Ashburner, John; Richard S. J. Frackowiak; Frith, Christopher D. (Proceedings of the National Academy of Sciences - PNAS, 2000)
Structural MRIs of the brains of humans with extensive navigation experience, licensed London taxi drivers, were analyzed and compared with those of control subjects who did not drive taxis. The posterior hippocampi of taxi drivers were significantly larger relative to those of control subjects. A more anterior hippocampal region was larger in control subjects than in taxi drivers. Hippocampal volume correlated with the amount of time spent as a taxi driver (positively in the posterior and negatively in the anterior hippocampus). These data are in accordance with the idea that the posterior hippocampus stores a spatial representation of the environment and can expand regionally to accommodate elaboration of this representation in people with a high dependence on navigational skills. It seems that there is a capacity for local plastic change in the structure of the healthy adult human brain in response to environmental demands.